2014
DOI: 10.1530/joe-14-0074
|View full text |Cite
|
Sign up to set email alerts
|

Androgens are bronchoactive drugs that act by relaxing airway smooth muscle and preventing bronchospasm

Abstract: Changes in the androgen levels in asthmatic men may be associated with the severity of asthma. Androgens induce a nongenomic relaxation in airway smooth muscle, but the underlying mechanisms remain unclear. The aim of this study was to investigate the potential bronchorelaxing action of testosterone (TES) and its metabolites (5a-and 5b-dihydrotestosterone (DHT). A preventive effect on ovalbumin (OVA)-induced bronchospasm was observed in sensitized guinea pigs for each androgen. Androgens were studied in respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 45 publications
2
42
0
1
Order By: Relevance
“…Our study adds the key evidence of the immuno-hormonal crosstalk in the pathogenesis of PMA, which is now considered one consistent with some earlier (25,26), but not with all (27,28) studies. The association between androgens and PMA has weakly been examined yet.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study adds the key evidence of the immuno-hormonal crosstalk in the pathogenesis of PMA, which is now considered one consistent with some earlier (25,26), but not with all (27,28) studies. The association between androgens and PMA has weakly been examined yet.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our findings, Wulfsohn et al demonstrated (28) that female asthmatic patients treated with testosterone demonstrated a 90% improvement of asthma symptoms, while Mileva et al (25) found low levels of serum testosterone in patients with severe (when compared with mild) asthma. The impact of testosterone on the function of lower airways might be explained by the results of the study by Monatano et al (26) who found that testosterone induces bronchial relaxation via blockage of calcium channels, thus relaxing airway smooth muscle and increasing the airflow. It is therefore possible that reduced serum testosterone level in PMA patients found in our study is one of the factors increasing BHR in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Androgens Androgens, such as testosterone, have an acute, non-genomic, and non-estrogenic effect on ASM activation (Kouloumenta et al 2006, Bordallo et al 2008, Montano et al 2014. The direction of the effect depends on the state of ASM activation.…”
Section: Gonadsmentioning
confidence: 99%
“…The direction of the effect depends on the state of ASM activation. On one hand, androgens relax pre-contracted ASM (Kouloumenta et al 2006, Bordallo et al 2008, Montano et al 2014 and potentiate the relaxing effect of b 2 -agonists (Foster et al 1983, Bordallo et al 2008, which suggest an overall bronchodilator effect. On the other hand, in the same ASM preparations and at the same concentrations, androgens potentiate the contractile response to a spasmogen, which suggest a constrictor effect (Bordallo et al 2008).…”
Section: Gonadsmentioning
confidence: 99%
See 1 more Smart Citation